2017
DOI: 10.1017/s0022226717000378
|View full text |Cite
|
Sign up to set email alerts
|

Cut(n) andcut(v) are not homophones: Lemma frequency affects the duration of noun–verb conversion pairs

Abstract: This paper tests whether lemma frequency impacts the duration of homographic noun–verb homophones in spontaneous speech, e.g. cut (n)/cut (v). In earlier research on effects of lemma frequency (e.g. Gahl 2008), these pairs of words were not investigated due to a focus on heterographic homophones. Theories of the mental lexicon in both linguistics and psycholinguistics differ as to whether these word pairs are assumed to have shared or separate lexical representations. An empirical analysis based on spontaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 47 publications
(88 reference statements)
5
27
0
Order By: Relevance
“…before the uniqueness point after which the morpheme discriminates the morphological function (Kemps et al, 005a;Balling and R. Baayen, 2008). The present results are therefore in line with a growing body of studies showing fine phonetic changes related to higher linguistic structures, especially morphology (Cho, 2001;Smith et al, 2012;Lee-Kim et al, 2012;Plag et al, 2017;Lohmann, 2017;Seyfarth et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…before the uniqueness point after which the morpheme discriminates the morphological function (Kemps et al, 005a;Balling and R. Baayen, 2008). The present results are therefore in line with a growing body of studies showing fine phonetic changes related to higher linguistic structures, especially morphology (Cho, 2001;Smith et al, 2012;Lee-Kim et al, 2012;Plag et al, 2017;Lohmann, 2017;Seyfarth et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…'thyme' vs 'time'). This finding was replicated by Lohmann (2017) for noun-verb homophoneous word pairs. Caselli et al (2016) showed that the acoustic durations of monomorphemic words (e.g.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Differences due to part of speech are largely attributable to phrase structure, as they are absent when items are placed in the same positions, e.g., sentencefinally (Conwell, 2017) and phrase-finally (Sorensen et al, 1978). The effects of lexical frequency have also sometimes been found to disappear when words are produced in isolation or in frame sentences (Guion, 1995); the most reliable effects are found within corpora of natural speech (e.g., Gahl, 2008;Lohman, 2017), and can be eliminated by controlling for other factors such as predictability based on context (Jurafsky, Bell, & Girand, 2002).…”
Section: Acoustic Details In Representationsmentioning
confidence: 99%
“…However, differences are found most reliably in natural speech (e.g. Gahl 2008;Lohman 2017), and can disappear when words are produced outside of their natural contexts. Differences correlated with lexical frequency can largely be eliminated by producing words in isolation or in frame sentences rather than in meaningful sentences (Guion 1995).…”
mentioning
confidence: 99%